ruminal fermentation and blood metabolites of growing goats fed ensiled Indigofera arrecta in complete diets - Simon P Ginting; A Tarigan; R Krisnan (Jurnal Ilmu Ternak dan Veteriner, 2012)
The study aimed to investigate the effects of offering different levels of ensiled  or fresh Indigofera arrecta in completete diets on the feed consumption, ADG, ruminal fermentation characteristics and blood metabolites concentrations in growing goats. The I. arrecta/concentrate ratios of the complete diets were set at 85/100,75/100 and 65/100. Thirty weaned-male goats were used in the study, and were randomly allocated to one of the six treatments (5 heads per treatment). The diets were offered at 4% BW and the animals were weighed weekly. The study was arranged  as a completed randomized design. Feed intake, average daily gain, feed efficiecy ratio, ruminal fermentation (pH, NH3 and VFA characteristics and blod metabolites (glucose and urea) were analysed. Feed intake of goats receiving ensiled Indigofera arrecta were lower (P < 0.01) compared to those receiving fresh I. arrecta. ADG were higher (P > 0.01) when goats were fed diets with lower level inclusion of Indigofera arrecta. Efficiency of feed utilization decreased (P < 0.01) when ensiled Indigofera arrecta was used in the diets, but it was not affected (P > 0.01) by the inclusion level of I. arrecta in the diets. Ruminal pH was not affected by ensiling process, but ruminal NH3 concentrations were greater (P < 0.01) in goats receiving fresh Indigofera arrecta. Ruminal VFA levels were also greater (P < 0.05) in the group offered fresh Indigofera arrecta, but the differences were not significant (P > 0.05) when diets consisted of 65% Indigofera arrecta in the complete diets. Increased  rate of Indigofera arrecta inclusion in the diets resulted in lower (P < 0.01) counts of ruminal microbial population. The concentration of plasma urea nitrogen were neither affected by the ensiling process nor by the levels of I. arrecta inclusion in the diet (P > 0.05), however, the plasma glucose level decreased (P < 0.05) as the level of I. arrecta inclusion in diets increased. It is concluded that I. arrecta could be used as the sole fresh or ensiled foliage in complete diets, although the performances of goats were better when  fresh I. arrecta was offered. The level of I. arrecta inclusion in complete diets was recommended at not greater than 65%. Key Words: I. arrecta, Silage, Complete Feed, Goat